Healthy Harvest: Florida’s Fruit and Vegetable Crops from the Farm to Your Plate - Catherine Campbell; Julia Graddy; Jeanette Andrade; Wendy Wilber (EDIS)
This publication provides an overview of the Healthy Harvest series. The series is for Florida residents who are interested in knowing more about crops that grow well in the state of Florida. Written by Catherine Campbell, Julia Graddy, Jeanette Andrade, and Wendy Wilber, and published by the UF/IFAS Department of Family, Youth and Community Sciences, June 2025.